Chemically Synthesized Alcaligenes Lipid A as an Adjuvant to Augment Immune Responses to Haemophilus Influenzae Type B Conjugate Vaccine - Liu, Zilai; Hosomi, Koji; Shimoyama, Atsushi; Yoshii, Ken; Sun, Xiao; Lan, Huangwenxian; Wang, Yunru; Yamaura, Haruki; Kenneth, Davie; Saika, Azusa; Nagatake, Takahiro; Kiyono, Hiroshi; et al. (Frontiers in Pharmacology, 2021)
We previously identified Alcaligenes spp. as a commensal bacterium that resides in lymphoid tissues, including Peyer’s patches. We found that Alcaligenes-derived lipopolysaccharide acted as a weak agonist of Toll-like receptor 4 due to the unique structure of lipid A, which lies in the core of lipopolysaccharide. This feature allowed the use of chemically synthesized Alcaligenes lipid A as a safe synthetic vaccine adjuvant that induces Th17 polarization to enhance systemic IgG and respiratory IgA responses to T-cell–dependent antigens (e.g., ovalbumin and pneumococcal surface protein A) without excessive inflammation. Here, we examined the adjuvant activity of Alcaligenes lipid A on a Haemophilus influenzae B conjugate vaccine that contains capsular polysaccharide polyribosyl ribitol phosphate (PRP), a T-cell–independent antigen, conjugated with the T-cell–dependent tetanus toxoid (TT) antigen (i.e., PRP-TT). When mice were subcutaneously immunized with PRP alone or mixed with TT, Alcaligenes lipid A did not affect PRP-specific IgG production. In contrast, PRP-specific serum IgG responses were enhanced when mice were immunized with PRP-TT, but these responses were impaired in similarly immunized T-cell–deficient nude mice. Furthermore, TT-specific—but not PRP-specific—T-cell activation occurred in mice immunized with PRP-TT together with Alcaligenes lipid A. In addition, coculture with Alcaligenes lipid A promoted significant proliferation of and enhanced antibody production by B cells. Together, these findings suggest that Alcaligenes lipid A exerts an adjuvant activity on thymus-independent Hib polysaccharide antigen in the presence of a T-cell–dependent conjugate carrier antigen.